La creatividad educativa y su impacto en el proceso de enseñanza aprendizaje en estudiantes de 4to año EGB de la Escuela Don Bosco, Mocache. 2022 - Herrera García, Luis Fernando (2022)
The present research work has been carried out at the "Don Bosco" school in the canton of Mocache, through it we have reached conclusions that allow us to affirm that creativity currently has a very important contribution in education because they are closely related. Through this study it was possible to identify that the lack of creativity in the classroom can generate problems such as low academic performance of students, poor concentration and little use of imagination to perform tasks and projects. It should be noted that students are a fundamental pillar of society because they are the future of the country, therefore, teachers are needed who are innovative in their teaching process and use dynamic methods when teaching their classes. That is why this study was conducted, because with it we can determine how the lack of educational creativity affects the classrooms in the institutions and in turn, the impact of the application of current educational resources in the teaching-learning process. Throughout this research some techniques that help in the creative development of students are mentioned, the conceptualization of the teaching process is also briefly explained and, of course, the importance of educational creativity. This work aims to illustrate how the teaching process affects students in the 4th year of general basic education at the Don Bosco school and thus serve as a resource that provides didactic strategies to help identify factors that prevent students from having a good academic performance and also improve the quality of the educational process